2016
DOI: 10.1038/npp.2016.201
|View full text |Cite
|
Sign up to set email alerts
|

TrkB Signaling in Dorsal Raphe Nucleus is Essential for Antidepressant Efficacy and Normal Aggression Behavior

Abstract: Brain-derived neurotrophic factor (BDNF) and its high affinity receptor, tropomyosin receptor kinase B (TrkB), have important roles in neural plasticity and are required for antidepressant efficacy. Studies examining the role of BDNF-TrkB signaling in depression and antidepressant efficacy have largely focused on the limbic system, leaving it unclear whether this signaling is important in other brain regions. BDNF and TrkB are both highly expressed in the dorsal raphe nucleus (DRN), a brain region that has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 46 publications
0
23
1
Order By: Relevance
“…Many studies have underscored serotonergic neurons in the DRN as a critical mediator of FLX actions (Adachi et al, 2016; Neumaier et al, 1996). Our tracing data reveals that VP PV neurons receive input from the DRN (Figure 2), which could alternatively explain how FLX treatment affects VP PV activity rather than direct effects on VP PV neurons themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have underscored serotonergic neurons in the DRN as a critical mediator of FLX actions (Adachi et al, 2016; Neumaier et al, 1996). Our tracing data reveals that VP PV neurons receive input from the DRN (Figure 2), which could alternatively explain how FLX treatment affects VP PV activity rather than direct effects on VP PV neurons themselves.…”
Section: Discussionmentioning
confidence: 99%
“…BDNF-TrkB not only affects the survival, development, and functions of neurons but also promotes the formation of the dendritic spine, provides a structural basis for synapse formation and improves the transmission efficiency of synapses. BDNF/TrkB signaling has a major impact on the production of antidepressant effects (44). Knock-out of the BDNF gene or the reduction of the levels of BDNF in the forebrain blocks the behavioral effects of antidepressants (45).…”
Section: Bdnf and Mood Disordersmentioning
confidence: 99%
“…Few studies have attempted to examine the concerted relative contributions of serotonin and dopamine towards discrete depressive-like behaviors. This is in spite of the fact that one of the main inputs to the VTA is the DRN (Beier et al, 2015; Faget et al, 2016; Watabe-Uchida et al, 2012) and alterations of this circuitry have been shown to mediate antidepressant efficacy (Adachi et al, 2017; Neumaier et al, 1996). Understanding how serotonergic inputs to the VTA can affect animals’ response to stress, especially in the context of depression, and how this input may modulate different downstream targets such as the LHb or dopaminergic signaling in the NAc or mPFC remain important questions to answer in the future.…”
Section: Monoaminesmentioning
confidence: 99%